Validation of a smartphone-based electrocardiography in the screening of QT intervals in children - Karacan, Mehmet (North Clin Istanb, 2019)
OBJECTIVE: A 12-lead electrocardiography is a critical component for the screening of long QT syndrome; however, besides, an electrocardiograph, trained personnel are also necessary which limits the screening capability of conventional electrocardiographs. The development of smartphone electrocardiography technologies provides a potential alternative platform for electrocardiography screening for selective purposes such as arrhythmias and QT interval abnormalities. The aim of this pilot study was to assess the reliability of a smartphone-based electrocardiography device in the measurement of QT and corrected QT intervals in children. METHODS: In all participants, 10-s smartphone electrocardiography tracing from AliveCor device and a standard 12-lead electrocardiograph were obtained simultaneously. Two pediatric electrophysiologists performed the measurements of QT and corrected QT intervals in a blinded manner with Bazett’s formula. The results were compared statistically. RESULTS: A total of 285 children (mean age 9.8±4.9 years) who presented to our clinic were included in the study. The mean QT intervals obtained from 12-lead electrocardiographs and AliveCor devices were 343±40 ms and 340±41 ms, respectively. The mean corrected QT intervals obtained from 12-lead electrocardiographs and AliveCor devices were 419±28 ms and 415±33 ms, respectively. There was high correlation between the QT intervals of 12-lead electrocardiographs and AliveCor recordings (Pearson’s correlation coefficient: 0.83 [p<0.001]) and significant correlation between the corrected QT intervals of 12-lead electrocardiographs and AliveCor recordings (Pearson’s correlation coefficient: 0.57 [p<0.001]). CONCLUSION: AliveCor recordings can accurately detect QT intervals and can potentially be used for the screening of congenital long QT syndrome in children.